2006
DOI: 10.1007/s11104-006-9035-1
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-dependent characterization of rhizobacterial communities from field grown Chinese cabbage Brassica campestris ssp pekinensis and screening of traits for potential plant growth promotion

Abstract: The composition of the bacterial community associated with plant roots is influenced by a variety of plant, environmental factors and also management practices. Our study aimed at detecting the root associated bacterial communities of Chinese cabbage under different fertilization regimes using cultivation dependent methods. The cultivable population was studied using plate count assay, fatty acid methyl ester (FAME) analysis and carbon substrate utilization (SU)using BIOLOG TM plates. Taxonomical identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
6
33
0
Order By: Relevance
“…Moreover, many authors report, that soil microbial communities are very plastic in composition and structure depending on different root zones, agricultural practices and environmental factors (Buckley & Schmidt 2003;Poonguzhali et al 2006). For example, Fang et al (2005) reported, that bacterial communities in maize rhizosphere were more affected by soil texture than by cultivation of transgenic cultivars.…”
Section: Carbon Substrate Utilization Pattern Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many authors report, that soil microbial communities are very plastic in composition and structure depending on different root zones, agricultural practices and environmental factors (Buckley & Schmidt 2003;Poonguzhali et al 2006). For example, Fang et al (2005) reported, that bacterial communities in maize rhizosphere were more affected by soil texture than by cultivation of transgenic cultivars.…”
Section: Carbon Substrate Utilization Pattern Analysismentioning
confidence: 99%
“…Several studies showed the effect of the plant species, plant growth stage, soil type, field management practices as well as other environmental factors on the rhizosphere communities (Bachmann & Kinzel 1992;Di Cello et al 1997;Smalla et al 2001;Grayston et al 2001;Harichová et al 2006;Poonguzhali et al 2006). Possible impacts of transgenic plants on rhizosphere microbial communities are of concern because little is known about diversity-function relationships of microorganisms associated with transgenic plants in the soil environment (Bruinsma et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the enzymic activities were assessed employing the API ZYM system (bio-M erieux). Utilization of polymeric substrates was qualitatively examined using Biolog GP2 MicroPlates as per previously published methodology [12,16,17]. The cellulose and xylose degradation potential of BL9…”
mentioning
confidence: 99%
“…Bacteria related to A. brasilense, are able to colonize bananas (Weber et al, 1999;Mia et al, 2010) and especially graminous plants, leading to an increase of 16 to 30% in the production of wheat and corn grains (Hungria et al, 2010). A. caulinodans strains promote growth in rice seedlings (Senthilkumar et al, 2008), and Sphingobium yanoikuyae strains have activity of indol acetic acid production (Poonguzhaly et al, 2006). Other endophytes related to Enterobacter oryzae (Peng et al, 2009), Pantoea eucrina and Erwinia sp.…”
Section: Discussionmentioning
confidence: 99%